1977
DOI: 10.1002/1097-0142(197711)40:5<1987::aid-cncr2820400502>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

One hundred cases of pheochromocytoma (107 tumors) at the columbia-presbyterian medical center, 1926-1976.A clinicopathological analysis

Abstract: Among 100 patients with pheochromocytoma there were 89 adults (sexes about even in distribution) and 11 children (7 boys; 4 girls). The right adrenal was involved 54 times, about twice the incidence on the left (29 times), and in three patients the tumors were bilateral. Seventeen had extra‐adrenal pheochro‐mocytomas, of which nine arose in the organ of Zuckerkandl. Only two of the 83 intra‐adrenal pheochromocytomas, or 2.4%, were malignant; whereas five of the extra‐adrenal tumors, or 30%, were cancerous. Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0
7

Year Published

1982
1982
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(94 citation statements)
references
References 38 publications
4
83
0
7
Order By: Relevance
“…In addition, malignant pheochromocytomas were nearly twice as large as benign tumours, with the former arising extraadrenally with greater frequency than the latter. Both observations confirm previous reports [9,12,13]. Twenty-four percent of the extraadrenal tumours in our study were malignant, versus only 8% of the intraadrenal tumours.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, malignant pheochromocytomas were nearly twice as large as benign tumours, with the former arising extraadrenally with greater frequency than the latter. Both observations confirm previous reports [9,12,13]. Twenty-four percent of the extraadrenal tumours in our study were malignant, versus only 8% of the intraadrenal tumours.…”
Section: Discussionsupporting
confidence: 93%
“…The malignancy rate of 6 to 20% reported by most authors [4][5][6][7][8][9][10][11][12][13][14] varies according to the definition of malignancy applied, i.e., metastasis, invasion of neighbouring organs, or invasion of organ capsules. Pheochro- Muenster, Germany mocytomas occur in less than 1 % of hypertensive individuals [15].…”
Section: Pheochromocytomasmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the incidence of malignant pheochromocytomas among 152 patients with pheochromocytomas was 11.2%, in good agreement with the 8% to 12.5% previously reported [7][8][9][10][11]. We also found that the 5-year survival rate of our patients with malignant pheochromocytoma was 11.8%, which was thus somewhat lower than the 20% previously reported [12].…”
Section: Discussionsupporting
confidence: 89%
“…The reported incidence varies from less than 1% to 19% of all pheochromocytomas (1)(2)(3)(4)(5), and when the primary lesion is extraadrenal, this may rise to 24% (6) or 30% (7). Recurrence usually occurs several years after removal of the primary tumor (5,8,9), and bone is the most commonsite for metastases (8).…”
Section: Introductionmentioning
confidence: 99%